ISOLASI DAN IDENTIFIKASI BAKTERI PENDEGRADASI SELULOSA ASAL EKOSISTEM MANGROVE TUKAK SADAI, BANGKA SELATAN - Ardiansyah Kurniawan; Dwi Febrianti; Suci Puspita Sari; Asep Awaludin Prihanto; Euis Asriani; Andi Kurniawan; Abu Bakar Sambah (Universitas Muhammadiyah Gresik, 2018)
Perikanan dan Kelautan, Universitas Brawijaya3Dosen Fakultas Perikanan dan Ilmu Kelautan, Universitas Brawijaya.ABSTRACTAgricultural waste has problems on fiber and cellulose digestibility in its utilization foraquaculture. The ability of plant cellulose degrading bacteria to become a source ofenergy can increase the digestibility of feed by fish. The purpose of this study was toidentify the cellulolytic bacteria from the mangrove ecosystem, Tukak Sadai District,South Bangka Regency. This study was conducted in March until August 2017.Samples were taken from litter, mud and weathered wood and isolated usingCarboxymetyl Cellulosa (CMC) 1% media and found 22 bacterial isolates. Gramstaining results showed that 3 isolates (TSS 2, TSL 6 and TSK 4) were classified asgram positive and 19 other isolates were gram negative. Cellulolytic test results showed6 isolates had the ability to degrade cellulase, namely 3 isolates from mangrove mudsamples (TSS 1, TSL 7, TSL 1), 2 isolates from leaf litter (TSS 4, TSL 2) and 1 isolatefrom weathered wood (TSK 5) . Sequencing of 16S rRNA gene DNA showed proximityto Pseudomonas aeruginosa in TSL 7 and TSS isolates 4